Magnetic Shielding at Low Frequencies: Application for an Aluminum/Steel Composite Elaborated by Accumulative Roll Bonding. Issue 4 (19th February 2019) - Verstraete, Kévin; Prévond, Laurent; Helbert, Anne‐Laure; Baudin, Thierry
Abstract : An IF steel/Al6061 composite elaborated by Accumulative Roll Bonding at room temperature is proposed for shielding effectiveness applications. The obtained composite is lighter than the copper and the steel with a density of 3–4.5. In the earlier rollings, a multilayered composite is developed which is in favor of strength but not of shielding. On the contrary, after 3 roll bondings, fragments of IF steel appear in the Al6061 matrix and drastically reduce strength but improve shielding. A finite element simulation of the shielding effectiveness is performed and Abstract : A steel/aluminum composite elaborated by Accumulative Roll Bonding is proposed for shielding effectiveness applications. The earlier rollings develop a multilayered composite which favors the strength but not shielding. Yet, after 3 roll bondings, steel fragments in the aluminum which drastically reduces the strength but improve the shielding. A finite element simulation of the shielding effectiveness confirms the experimental results.